المسؤولية الاجتماعية للمؤسسة الاصلاحية تجاه العاملين [دراسة ميدانية في مديرية اصلاح النساء والاحداث في مدينة السليمانية] - غفور, رزگار مصطفی (Sulaimani Journal for Humanities, 2025)
The issue of social responsibility of the reform institution towards the working staff focuses on the tasks and obligations including providing them all necessary services and facilities in order to perform their work in the best way in order to ensure the effectiveness of these institutions and to promote their performance because the workers represent an important human resource in these institutions and most of the burden falls on these workers to achieve the objectives of the reform institution. Accordingly, elevating the standard of social responsibility by the reform institution towards its working staff contributes in developing and improving their performance and the level of those institutions' effectiveness. This study aims at: 1) Identify the social responsibility of the reform institution towards the workers. 2) Identify the indicator of the statistical differences of the social responsibility in the reform institution towards the workers according to the variables of (gender, age, educational attainment and occupation). The research is a descriptive one in which social survey is used through employing a sample method. The study community consists of the workers who have direct contact with the inmates in the Directorate of the Women and Juveniles Reform in the city of Sulaymaniyah, which include the officer, the supervisor and wardens, who totally amount 134 persons as the main burden is on the working staff in achieving the goals of the reform institution. Among these workers 60 (rated 44.77%) has been intentionally selected. In order to achieve the objectives of the study and then to apply the questionnaire form, that consists of 23 questions, on the sample of the study in the Directorate of Women and Juveniles Reform in the city of Sulaymaniyah, the researcher conducted measures of accuracy and reliability of the questionnaire form in order to be applied to the respondents using statistical methods. The study concluded the following: 1. The results show that the social responsibility of the reform institution is not at the required level. This has been shown by the respondents' answers that indicated the failure of the reform institution to fulfill its responsibilities as required. 2. The results of the study show satisfaction with the level of social responsibility of the reform institution in relation to the gender variable in favor of females, as they have expressed their positive opinion about the performance of social responsibilities of the reform institution, while males have indicated that the social responsibility in the reform institution is not at the required level. 3. The results of the study show that the social responsibility of the reform institution in relation to the variables of age, educational attainment and occupation is not at the required level. The respondents indicated that the reform institution does not provide necessary services and facilities as they dhould be. In the light of these results, the researcher presented a number of recommendations and suggestions to promote the level of social responsibility in the reform institutions.